The Increased Levels of Fecal Calprotectin in Children With Active Enthesitis Related Arthritis and MRI Signs of Sacroiliitis: The Results of a Single Center Cross-Sectional Exploratory Study in Juvenile Idiopathic Arthritis Patients - Lamot, Lovro; Miler, Marijana; Vukojević, Rudolf; Vidović, Mandica; Lamot, Mirta; Trutin, Ivana; Gabaj, Nora Nikolac; Harjaček, Miroslav (Frontiers in Medicine, 2021)
Enthesitis related arthritis (ERA) is a specific subtype of juvenile idiopathic arthritis (JIA), often regarded as an undifferentiated form of juvenile spondyloarthritis (jSpA). While gut is increasingly recognized as origin and/or target of inflammation in adult onset spondyloarthritis (SpA), the incidence of gut involvement in ERA patients is largely unknown. The aim of this study was to measure the concentration of faecal calprotectin (fCAL), a surrogate marker of gut inflammation, in patients with different subtypes of JIA, as well as to correlate the results with various demographic, clinical, laboratory, imaging and treatment characteristics. The cross-sectional exploratory study involving 71 patients with ERA, other forms of JIA and children complaining musculoskeletal symptoms was therefore conducted. Along with fCAL assessment, detailed clinical and laboratory examination was performed, including the calculation of a composite disease activity scores. Moreover, MRI of the sacroiliac joints was performed in all ERA and other patients complaining of low back pain. The median concentration of fCAL was highest in ERA patients (33.2 mg/kg, p=0.02), with a significant difference between those with inactive and active disease (20.0 vs 57.4, p=0.01), as well as those with and without MRI signs of sacroiliitis (22.6 vs 54.3, p=0.04). The fCAL did not differ depending on the NSAID use (23 vs 20, p=0.18), although weak correlation was observed with the treatment duration (r=0.25, p=0.03). In conclusion, our findings indicate that a parallel inflammation in musculoskeletal system and gut can occur not just in adults with SpA, but in children with ERA as well.